The narconovela and crime in Colombia - Galindo, Carolina (Anthropos (Ljubljana), 2025)
This article analyses the origins of the narconovela (narcosoap opera) in Colombia, focusing on the controversy caused, at the start of the 1980’s, by the soap opera entitled La mala hierba (The Evil Weed). Through an analysis of its reception during the time it was on the air, some links with the current discussion about this genre will be established, along with some links with its impact on the legitimization of narcotics trafficking and crime in Colombia and Latin America in recent years.
Keywords: crime; drug traffickingin Colombia; kriminal; Latin America; Latinska Amerika; narconovela(narco-soapopera); narkonovela (narkotelenovela); trgovina z mamili v Kolumbiji